Polypharmacy and potentially inappropriate medication in elderly of Northern Portugal - Pinto, Isabel C. (2015)
Introduction The growing aging of population and increasing prevalence of chronic diseases require the simultaneous use of drugs, lead to the issue of polypharmacy and potentially interactions and inappropriate use. Aim To characterize polymedicated elderly and related factors, identify potentially interactions and inappropriate medication in elderly. Material and Methods This cross-sectional study was based on a questionnaire applied to 69 elderly (≥65 years) from northern Portugal. It was considered as polymedicated seniors taking ≥5 drugs. Beers list and the Delafuente classification were used to evaluate the therapeutic and possible interactions. It was used descriptive statistics and a model of binary regression, with a significance of 5%. The study was approved by Ethics Committee. Results The sample consisted mainly of males (53.6% vs. 46.4%), aged between 66 and 99 years (mean 82.01), while 65.2% have more than 80 years. However, most elderly are not polymedicated (58%), on average 4.61 different drugs are administered per day (maximum=19), antihypertensives (36.2%) and antacids (30.04%) are the most prescribed. Hypertension and depression increase the risk of polymedication eightfold (P = 0.004) and fivefold (P = 0.011) respectively. Female gender seems increase the risk of polypharmacy threefold, although not statistically significant (P = 0.102), and regarding age, the older age group (>85 years) seems reduces the risk of polypharmacy in 0.6 fold, but also not statistically significant. According with Delafuente classification, 1.4% of elderly has potentially drug interactions (Omeprazole and Iron salts). According to the list of Beers, 5.8% of seniors take drugs that classified as having some indications (hydroxyzine, amitriptyline). Conclusions Regarding polypharmacy, 42% of elderly are polymedicated with an average of about 5 different drugs per day, antihypertensives and antacids the most prescribed. Hypertension and depression are highly associated with polypharmacy. We identified one potentially drug interaction and about 6% of elderly taking drugs that classified as having some indications.